Caregiver use of MUAC tapes in South Sudan: a three-group prospective comparison - Doocy, Shannon; Ismail, Sule; Lyles, Emily; Altare, Chiara; Bauler, Sarah; Obali, Francis; Atem, Daniel; Leidman, Eva; , The South Sudan MUAC Study Team (Frontiers in Nutrition, 2024)
Introduction: Nutrition program modifications occurred globally in response to the COVID-19 pandemic. Within community management of acute malnutrition (CMAM), community screenings for acute malnutrition were replaced by caregivers monitoring child mid-upper arm circumference (MUAC), but questions remain about different MUAC tapes’ performance and acceptability for caregiver use. Methods: The study was conducted in Central Equatoria and Warrap States, South Sudan between March 2022 and January 2023. A 3-group prospective non-randomized design was used to compare performance of 3 MUAC tapes (UNICEF 2009, UNICEF 2020, GOAL MAMI) used by caregivers. The primary outcome was the false negative rate (i.e., proportion of children not identified as wasted by the caregiver but classified as wasted by enumerators). Caregivers with children 5-53 months were assigned to and trained on use of 1 of the 3 tapes and followed for 8 months including 3 monitoring visits and baseline/endline surveys. Results: Of the 2,893 enrolled children, 2,401 (83.0%) completed baseline, endline, and 2 or more monitoring visits. Only 3.7% of children were identified as wasted by caregivers, and 3.8% by study team measurement. Cumulative measurement agreement between caregivers and enumerators was similar by tape. False negative and false positive rates were both <0.5% overall and similar among the tapes. There were differences in training needs and durability between the tapes, but all 3 were acceptable and performed equally well. Discussion: Caregiver measurement of child MUAC is feasible in South Sudan. The 3 MUAC tapes were acceptable, and caregivers could measure accurately with minimal support. All tapes performed similarly and are appropriate for use in Family MUAC programs in South Sudan. There were indications that the UNICEF 2020 tape may be less durable; the GOAL MAMI tape has the added benefit of being suitable for assessments of infants <6 months of age.